Relationship Of Knowledge And Attitude Toward Prevention Of HIV And AIDS Behavior At Cafe Pramusaji In Tanjung Bira - Andi Suswani; Irfanita Nurhidayah; Wiwis Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
AIDS or Acquired Immuno Deficiency Syndrome is a collection of symptoms that arise due to decreased immunity caused by infection by HIV. As a result of decreased immunity, the person is very susceptible to various infectious diseases that are often fatal. With a healthy lifestyle, the time between HIV infection and becoming ill with AIDS can range from 10-15 years, sometimes even longer. Not having sexual intercourse with an infected person, especially anal intercourse, ie body fluids, blood, semen or vaginal secretions most likely to be exchanged, is the only 100% effective way to prevent HIV transmission through sex. The purpose of this study is to determine the relationship of knowledge, attitudes with HIV and AIDS prevention behavior in Cafe Waiters in Tanjung Bira, Bontobahari District, Bulukumba Regency. This study uses an analytic observational design with a